Role of Natural Gas Supply Sector in the National Economy: A Comparative Analysis between South Korea and Japan - Seo-Young Lee; Ju-Hee Kim; Seung-Hoon Yoo (Applied Sciences, 2023)
This study examines the role of the natural gas supply sector in the national economy by applying input–output analysis to South Korea and Japan. Specifically, the production-inducing effect, value-added creation effect, wage-inducing effect, employment-inducing effect, supply shortage effect, and price-inducing effect were analyzed using an input–output table of South Korea and Japan. As a result, the production-inducing effect, value-added creation effect, and employment-inducing effect of same investment amount in the natural gas supply sector were greater in Japan than in South Korea. On the other hand, the wage-inducing effect of an investment of USD 1 in the natural gas supply sector was found to be greater in South Korea than in Japan. In addition, the supply shortage effect and price-inducing effect in the natural gas supply sector were greater in South Korea than in Japan. The causes of differences in analysis results for each country and their implications were discussed. The results of this study could be a useful reference for the government to establish policies related to natural gas supply in the future.